2022
DOI: 10.1186/s12879-022-07303-8
|View full text |Cite
|
Sign up to set email alerts
|

Enigma of COVID-19: is “multisystem inflammatory syndrome in adults” (MIS-A) predictable?

Abstract: Background Severe inflammation and one or more extrapulmonary organ dysfunctions have been reported and this clinical picture is defined as "multisystem inflammatory syndrome in adults" (MIS-A) in severe coronavirus disease-2019 (COVID-19). We aimed to determine the effect of LDH/lymphocyte ratio (LLR) on the development of MIS-A. Methods The data of 2333 patients were retrospectively analyzed. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 28 publications
(25 reference statements)
0
11
0
Order By: Relevance
“…First identified in April 2020, MIS seemed to happen more commonly to children. However, recent studies on MIS showed that MIS also occurred in 9.9% of the infected adults age > 21 [12] , and thus the diagnosis of adult type (MIS-A) was established. As previously reported and our case presented, MIS-A commonly occur during the period of recovery after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…First identified in April 2020, MIS seemed to happen more commonly to children. However, recent studies on MIS showed that MIS also occurred in 9.9% of the infected adults age > 21 [12] , and thus the diagnosis of adult type (MIS-A) was established. As previously reported and our case presented, MIS-A commonly occur during the period of recovery after SARS-CoV-2 infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, 42 (79.2%) patients required intensive care unit (ICU) admission, and 23 (43.4%) patients died 26 . A large single cohort study in Turkey reported that MIS‐A‐related mortality was 35.3% (82/233), and using the LDH/lymphocyte cutoff value of 0.32 can help predict mortality with 78% sensitivity and 70% specificity 32 . Based on Patel et al's 16 review, 110 (51%) of 214 and 101 (47%) of 213 patients required vasoactive medication and respiratory support, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Serin et al 32 conducted a large single‐center retrospective study in Turkey. They identified 232 (9.9%) cases of MIS‐A among 2333 hospitalized patients with COVID‐19 between March and December 2020 32 . The mean age was 62.1 years, and 143 (61.6%) patients were male.…”
Section: Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The typical clinical presentation of MIS-A is fever and signs of inflammation [ 5 ]. While the identification of MIS-A is difficult, elevated inflammatory markers including C-reactive protein (CRP), ferritin, D-dimer, and interleukin (IL)-6 serve as valuable indicators for clinicians [ 6 ]. At present, definitive treatment for MIS-A remains unclear.…”
Section: Introductionmentioning
confidence: 99%